On the instability of private intertemporal liquidity provision - Dietrich, Diemo; Gehrig, Thomas (Economics letters, 2021)
The provision of intertemporal liquidity by banks is known to be subject to coordination failures. We establish that asset markets providing intertemporal liquidity are also inherently unstable. These findings challenge the notion of an optimal private provision of liquidity.